Study protocol for a multi-center, randomized controlled trial to develop Japanese denture adhesive guidelines for patients with complete dentures: the Denture Adhesive Guideline trial: study protocol for a randomized controlled trial. Issue 1 (December 2016) - Kimoto, Suguru; Kawai, Yasuhiko; Gunji, Atsuko; Kondo, Hisatomo; Nomura, Taro; Murakami, Tomohiko; Tsuboi, Akito; Hong, Guang; Minakuchi, Shunsuke; Sato, Yusuke; Ohwada, Gaku; Suzuki, Tetsuya; et al.
Abstract Background Denture adhesives, characterized as medical products in 1935 by the American Dental Association, have been considered useful adjuncts for improving denture retention and stability. However, many dentists in Japan are hesitant to acknowledge denture adhesives in daily practice because of the stereotype that dentures should be inherently stable, without the aid of adhesives. The aim of this study is to verify the efficacy of denture adhesives to establish guidelines for Japanese users. The null hypothesis is that the application of denture adhesives, including the cream and powder types, or a control (isotonic sodium chloride solution) would not produce different outcomes nor would they differentially improve the set outcomes between baseline and day 4 post-application. Methods This ten-center, randomized controlled trial with parallel groups is ongoing. Three hundred edentulous patients with complete dentures will be allocated to three groups (cream-type adhesive, powder-type adhesive, and control groups). The participants will wear their dentures with the denture adhesive for 4 days, including during eight meals (three breakfasts, two lunches, and three dinners). The baseline measurements and final measurements for the denture adhesives will be performed on the first day and after breakfast on the fourth day. The primary outcome is a general satisfaction rating for the denture. The secondary outcomes are denture satisfaction ratings for various denture functions, occlusal bite force, resistance to dislodgement, masticatory performance, perceived chewing ability, and oral health-related quality of life. Between-subjects comparisons among the three groups and within-subjects comparisons of the pre- and post-intervention measurements will be performed. Furthermore, a multiple regression analysis will be performed. The main analyses will be based on the intention-to-treat principle. A sample size of 100 subjects per group, including an assumed dropout rate of 10 %, will be required to achieve 80 % power with a 5 % alpha level. Discussion This randomized clinical trial will provide information about denture adhesives to complete denture wearers, prosthodontic educators, and dentists in Japan. We believe this new evidence on denture adhesive use from Japan will aid dentists in their daily practice even in other countries. Trial registration ClinicalTrials.govNCT01712802 . Registered on 17 October 2012.